Footprint of Deepwater Horizon blowout impact to deep-water coral communities - Fisher, Charles R. (National Academy of Sciences, 2014)
On April 20, 2010, the Deepwater Horizon (DWH) blowout occurred, releasing more oil than any accidental spill in history. Oil release continued for 87 d and much of the oil and gas remained in, or returned to, the deep sea. A coral community significantly impacted by the spill was discovered in late 2010 at 1,370 m depth. Here we describe the discovery of five previously unknown coral communities near the Macondo wellhead and show that at least two additional coral communities were impacted by the spill. Although the oil-containing flocullent material that was present on corals when the first impacted community was discovered was largely gone, a characteristic patchy covering of hydrozoans on dead portions of the skeleton allowed recognition of impacted colonies at the more recently discovered sites. One of these communities was 6 km south of the Macondo wellhead and over 90% of the corals present showed the characteristic signs of recent impact. The other community, 22 km southeast of the wellhead between 1,850 and 1,950 m depth, was more lightly impacted. However, the discovery of this site considerably extends the distance from Macondo and depth range of significant impact to benthic macrofaunal communities. We also show that most known deep-water coral communities in the Gulf of Mexico do not appear to have been acutely impacted by the spill, although two of the newly discovered communities near the wellhead apparently not impacted by the spill have been impacted by deep-sea fishing operations.